Concession-making in multi-bilateral negotiations and multi-attribute auctions - Kersten, Gregory (Grzegorz) E.; Gimon, Dmitry (Decyzje o ustępstwach w wielo-dwustronnych negocjacjach oraz wielokryterialnych aukcjach, 2012)
Reverse auctions and negotiations are two common procurement mechanisms. The drawback of many auctions is their sole focus on price. The drawback of negotiations is that they are sequential, slow and costly. The Internet enables multi-attribute auctions and multi- -bilateral multi-attribute negotiations efficiently. In both processes concession-making plays a key role. The paper presents typology of concessions, which has been empirically verified. The results show that: (1) bidders and negotiators use all types of permissible concessions; (2) bidders make more concessions in auctions than in negotiations; and (3) the use of singleand multiple-attribute concessions differs between auctions and negotiations. The results also show that buyers obtain the highest profit through auctions, then competitive negotiations and the lowest through cooperative negotiations. The reverse is true for the sellers
Informatyka Ekonomiczna = Business Informatics, 2012, Nr 3 (25), s. 61-83
Keywords: reverse auctions; multi-attribute auctions; multi-bilateral negotiations; concesion-making; behavioral experiments; aukcje odwrotne; aukcje wieloatrybutowe; negocjacje wielo-dwustronne; ustępstwa; eksperymenty